A new genus of carnivorous sponges (Porifera: Poecilosclerida, Cladorhizidae) from the deep N-E Pacific, and remarks on the genus Neocladia - Vacelet, Jean (Zootaxa, 2008)
A new sponge collected from 2,024 m depth on the Vance Seamount in the north-east Pacific by the ROV ‘Tiburon’ is described in the family Cladorhizidae as a new genus and new species, Lollipocladia tiburoni. The sponge, 112 mm in total height, is in the shape of a pedunculate disc, like several cladorhizid sponges of the genera Abyssocladia and Neocladia. It differs from these genera and from all carnivorous poecilosclerids by its microsclere complement, consisting of palmate isochelae, sigmancistras, and strongly curved anchorate isochelae superficially resembling those of Neocladia. A re-examination of the holotype of Neocladia indicates that it is a valid genus different from Chondrocladia.